Guidelines for the use of platelet transfusions - Estcourt, L; Birchall, J; Allard, S; Bassey, S; Hersey, P; Kerr, J; Mumford, A; Stanworth, S; Tinegate, H (Wiley, 2016)
The demand for platelets in England was stable at around 220,000 adult therapeutic doses (ATD) per year until 2007/8 at which point demand has increased year on year to 275,000 ATD in 2014/15, an increase of 25%. Similar rises in demand have been seen in Australia and the United States. A recent review which considered causes for this dramatic rise identified that an ageing population and an increase in the incidence of haematological malignancies (with increased treatment intensity, duration and survival) accounted for most of this change (Estcourt 2014). This guideline aims to provide practical advice on platelet transfusions to help clinicians to decide when support is expected to be beneficial and to reduce inappropriate use.